Some ecological and faunistical notes on insect fauna in Şahaplı stream (Turkey: Elazığ: Baskil) - Özgen, İnanç; Topdemir, Aykut; Tanyıldızı, M. Şaban (My University, 2017)
Şahaplı is located in the south of Baskil district, Şevkat creek merging with the River Geli which is stemming from the creeks of Bulutlu Mountain near Keluşağı, is the river flows into Karakaya dam lake (Anonymous, 2016). In recent years, the stream has been affected by domestic pollutants. Sewage wastes of Baskil are poured into this quarry. Because of this, biodiversity and its varieties in this stream and its vicinity are important. A detailed study on insect biodiversity in the vicinity of this stream has not been done yet. This study includes the results of surveys carried out in certain periods to determine insect biodiversity nearby the stream. In the study, glass jars with a diameter of 5 cm and a height of 10 cm were placed at the edge of the creek so that the tubulure part would be on the same surface as the soil layer. Ethylene glycol, vinegar or antifreeze was poured into the jars at a height of 4 cm and water was added to the other 4 cm clearance. The liquids in the jar-traps were brought to the laboratory by draining them into the culture jars with the aid of a strainer for 15 days. Species were separated into the family level and sent to experts for diagnosis. Besides, atrap sampling method has also been applied in order to collect the species found on weeds at the stream’s waterfront. The study was carried out between April and October of 2015-2016.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Şahaplı stream; Insect fauna